Understanding the role of Shroom3 in the developing mouse myocardium - Jennifer L. Carleton; Rami R. Halabi; Jessica A. Willson; Timothy F. Plageman Jr.; Darren Bridgewater; Qingping Feng; Thomas A. Drysdale (PLoS ONE, 2025)
Loss of actin cytoskeleton control can hinder integral developmental and physiological processes and can be the basis for a subset of developmental defects. SHROOM3 is an actin binding protein, best characterized as being essential for neural tube closure in vertebrates. Shroom3 expression has also been identified in the developing heart, with some associated congenital heart defects. Here we show that the expression pattern of Shroom3 in the developing and adult mouse heart is specific to the myocardium. Using a gene trap line, we show that embryos with homozygous full-body Shroom3 loss die at birth due to exencephaly but also show congenital heart defects. This includes ventricular septal defects, semilunar valve abnormalities, and ventricle wall thinning. Adult mice heterozygous for Shroom3 loss also show ventricular thinning due to decreased cardiomyocyte size. To explore if SHROOM3 is operating in a cell autonomous manner in the cardiomyocytes, we utilized a floxed Shroom3 mouse line, allowing for spatial and temporal control of Shroom3 loss. Using an Nkx2–5-Cre recombinase, we targeted Shroom3 loss to the myocardium of the developing heart. Neonate pups with myocardial specific Shroom3 loss showed no significant impact on heart development, including no septal or valve defects, no ventricular thinning, and no change in viability into adulthood. Adult mice with myocardial specific Shroom3 loss showed no ventricular thinning and no change in cardiomyocyte size. These results show that the heart defects seen in full-body Shroom3 loss do not arise from myocardial specific loss. Rather, other cell types expressing Shroom3 , such as the cardiac neural crest cells, may be directly contributing to cardiac development.